Faktor Risiko yang Berhubungan dengan Kematian Pasien Penyakit Ginjal Kronis pada Usia Dewasa yang Menjalani Hemodialisis Reguler di Provinsi Lampung - Latupeirissa, Joue Abraham Trixie; Sudaryo, Mondastri Korib; Hadiaturahman, Muhamad Zulfikar; Sinaga, Steven Sapta Putra (Jurnal Penyakit Dalam Indonesia, 2025)
Introduction. Although mortality among adult chronic kidney disease (CKD) patients on regular hemodialysis remains infrequent within the first three months, it is still a potential outcome. Given that hemodialysis is required for life, identifying risk factors for mortality is critical. This study aims to examine risk factors associated with mortality in adult CKD patients undergoing regular hemodialysis. Methods. A case-control study, without matching, was conducted using medical record data from adult CKD patients (≥18 years) receiving regular hemodialysis between 2022 and 2024 at three hospitals (types A, B, and C) in Lampung Province. The case group consisted of patients who experienced mortality, while the control group consisted of similar patients who survived. Patients with autoimmune-related CKD were excluded. Subjects were selected using convenience sampling with a 1:2 case-to-control ratio. Risk factors assessed included sociodemographics, dialysis duration, comorbidities, and nutritional status. Logistic regression analysis was performed. Results. A total of 114 cases and 228 controls were included, with the longest dialysis duration in both groups being 72 months. The oldest patient starting dialysis was 77 years in the case group and 75 years in the control group. Logistic regression analysis revealed that the following factors were associated with increased mortality: history of heart failure (OR = 2.3; 95% CI = 1.2–4.4; p = 0.009), history of post-renal obstruction (OR = 3.5; 95% CI = 1.6–7.6; p = 0.002), random blood glucose ≥140 mg/dL (OR = 2.1; 95% CI = 1.2–3.6; p = 0.011), acute kidney injury (OR = 6.5; 95% CI = 3.8–11.1; p < 0.001), and BMI Conclusion. History of heart failure, post-renal obstruction, elevated blood glucose, acute kidney injury, and low BMI are significant predictors of mortality in adult CKD patients undergoing regular hemodialysis in Lampung Province.